2014
DOI: 10.1109/tsp.2014.2321733
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Energy Allocation for Energy Harvesting Transmitters With Hybrid Energy Storage and Processing Cost

Abstract: Abstract-We consider data transmission with an energy harvesting transmitter that has hybrid energy storage with a perfect super-capacitor (SC) and an inefficient battery. The SC has finite storage space while the battery has unlimited space. The transmitter can choose to store the harvested energy in the SC or in the battery. The energy is drained from the SC and the battery simultaneously. In this setting, we consider throughput optimal offline energy allocation problem over a point-to-point channel. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…It can be shown that the problem (21) is a relaxed version of (9). Specifically, any feasible solution of (9), satisfying (5)- (8), ∀t, also satisfies (19) and (20), due to the relevant optimization variables. It then follows thatŨ opt ≥ U opt .…”
Section: Optimality Gapmentioning
confidence: 99%
“…It can be shown that the problem (21) is a relaxed version of (9). Specifically, any feasible solution of (9), satisfying (5)- (8), ∀t, also satisfies (19) and (20), due to the relevant optimization variables. It then follows thatŨ opt ≥ U opt .…”
Section: Optimality Gapmentioning
confidence: 99%
“…While the PV system location is typically constrained by land requirements and availability, the BESS location is much more flexible. In general, BESS' allocation methods can be divided into two groups: 1) optimum battery operation [17]- [20] and 2) optimum microgrid operation [21]- [29]. In the first category, objectives such as installation [17], maintenance [18], and operation [19] are considered.…”
Section: Introductionmentioning
confidence: 99%
“…The BS and the UEs all conceive a single antenna and they operate on the same spectral band, which indicates that all the spatial resources and frequency resources are multiplexed by the UEs. Moreover, the UEs in the DEIN are equipped with super capacitors [22]. Super capacitors may ideally store the energy that is extracted from RF signals without any energy loss.…”
Section: Introductionmentioning
confidence: 99%